2022
DOI: 10.1155/2022/8557936
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Early Acupuncture Combined with Rehabilitation Training on Limb Function and Nerve Injury Rehabilitation in Elderly Patients with Stroke: Based on a Retrospective Cohort Study

Abstract: Objective. A case-control study was conducted to explore the effect of acupuncture combined with rehabilitation training on limb function and nerve injury rehabilitation in elderly patients with stroke. Methods. A total of 72 elderly patients with stroke treated from March 2019 to June 2021 in our hospital were enrolled as the object of study. The clinical data were collected and divided into two groups according to their different treatment methods. The patients cured with routine treatment combined with reha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…Meanwhile, compared with conventional nursing, professional early rehabilitation nursing, such as psychological rehabilitation, diet and traditional Chinese medicine intervention, is more conducive to the rehabilitation of patients. [37][38][39] The routine nursing scheme mainly consists of basic nursing contents such as exercise, diet guidance and health education. Such scheme is too single and boring to obtain satisfactory nursing effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, compared with conventional nursing, professional early rehabilitation nursing, such as psychological rehabilitation, diet and traditional Chinese medicine intervention, is more conducive to the rehabilitation of patients. [37][38][39] The routine nursing scheme mainly consists of basic nursing contents such as exercise, diet guidance and health education. Such scheme is too single and boring to obtain satisfactory nursing effect.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, compared with conventional nursing, professional early rehabilitation nursing, such as psychological rehabilitation, diet and traditional Chinese medicine intervention, is more conducive to the rehabilitation of patients. [37–39]…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Studies have shown that about 70% of patients have motor dysfunction after stroke, and 14% to 71% have swallowing dysfunction. 4 Modern medicine has explored the mechanism of body dysfunction after stroke. Based on these studies, various treatment programs such as feeding training, functional exercise of muscles related to swallowing, pharyngeal stimulation, and surgery have been developed, all of which have achieved different results.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a systematic review and metaanalysis demonstrated that TENS was related to the improvement of spasticity and promoted walking speed and static balance in stroke patients [22]. Actually, increasing evidence supports early rehabilitation interventions after stroke are of important significance, which can rebuild brain function, accelerate the average cerebral blood flow, and promote collateral circulation formation, thus improving the neurological function of patients [23][24][25][26][27]. Therefore, clarifying whether and how TENS exerts beneficial effects at the early stage of ischemic stroke will provide theoretical basis and promote the extensive application of TENS in clinic.…”
Section: Introductionmentioning
confidence: 99%